2019
DOI: 10.21608/jppp.2019.40557
|View full text |Cite
|
Sign up to set email alerts
|

Survey, Population Dynamics and Estimation of Damage of Common Land Snail Species on Some Vegetable Plants and Egyptian Clover at Some Regions at Kafr El-Sheikh Governorate

Abstract: Survey and population dynamics were carried out in two regions, Abu-Abdalla village, Sedi Salem District and Salait village, Quallen district at Kafr El-Sheikh Governorate during two successive seasons from 2015to2017 on egyptian clover, lettuce, and cabbage. The survey revealed the existence of four species of land snails, Monacha cantiana, Succinea putris, Theba pisana and Cochlicella acuta were predominant on egyptian clover and two vegetables crops. The population densities of these land snail species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Generally, the species Succinea sp. documented in South district of Port Saied, Port Saied governorate (Awad, 2013), Ismailia and Sharkia (Rady, 2014), Qalyubia, Monufia, Sharkia, Damietta, and Dakahlia (Mohammed, 2015), and Kafr El-Sheikh governorate (Gazzy et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the species Succinea sp. documented in South district of Port Saied, Port Saied governorate (Awad, 2013), Ismailia and Sharkia (Rady, 2014), Qalyubia, Monufia, Sharkia, Damietta, and Dakahlia (Mohammed, 2015), and Kafr El-Sheikh governorate (Gazzy et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Succinea sp. had been recorded on lettuce, Egyptian clover, rice, broad bean, pea and cabbage (Mohammed, 2015;Heiba et al, 2018;Gazzy et al, 2019) and also recorded mainly on field and vegetables, and not had recorded on ornamental plants or wood trees in Kafr El sheikh governorate (Heiba et al, 2018). In this study, Succinea (Amphibina) Cleopatra found on Chicory Cichorium pumilum and Egyptian clover Trifolium alexandrinum at El Qanater El Khayreya (coordinates 30°11.601' N 31°06.693' E) ( Fig.…”
Section: Host Range and Habitatmentioning
confidence: 99%
See 3 more Smart Citations